Ultrathin two-dimensional porous organic nanosheets with molecular rotors for chemical sensing. Issue 1 (December 2017) - Dong, Jinqiao; Zhang, Kang; Li, Xu; Qian, Yuhong; Zhu, Hai; Yuan, Daqiang; Xu, Qing-Hua; Jiang, Jianwen; Zhao, Dan
Abstract Molecular rotors have played an important role in recent materials chemistry. Although several studies on functional materials containing molecular rotors have been reported for fluorescence sensing, this concept has yet to be realized in two-dimensional (2D) materials. Here we report the preparation of all-carbon, π-conjugated 2D porous organic nanosheets, named NUS-24, which contain flexible tetraphenylethylene (TPE) units as the molecular rotors. NUS-24 nanosheets exhibit high stability, large lateral size, and ultrathin thickness (2–5 nm). The dynamic TPE rotors exposed on the surface of NUS-24 nanosheets can be restricted in the aggregated state with different water fractions, which is reminiscent of the aggregation-induced emission mechanism, thereby leading to the size-selective turn-on fluorescence by volatile organic compounds. Significantly, the ultrathin 2D nanosheets and its composite membranes show much higher sensitivity and selectivity toward Fe3+ ions and nitro-containing compounds sensing, suggesting their potential applications in explosive detection and environmental monitoring. Molecular rotors that fluoresce upon restriction are useful components in functional materials. Here, the authors incorporate molecular rotors into 2D porous organic nanosheets, creating sensitive and selective fluorescent sensors for volatile organic compounds and metal ions.